Pembinaan Karakter Nasionalisme Siswa Sekolah Dasar dengan Pembiasaan Menyanyikan Lagu Indonesia Raya - Windy Prasetya Puspitasari; Citra Bintang Maharani; Kartika Dwi Pertiwi; Siti Syaira (Jurnal Ilmiah Wahana Pendidikan, 2023)
This journal is based on the eroding sense of nationalism which is increasingly fading among students in elementary schools which has made the inculcation of nationalist values ​​in the world of education now begun to be increased. Nationalism character education is an effective step to build a sense of nationalism for future generations. This journal aims to find out the development of the character of nationalism, the supporting factors, the obstacles experienced, and how to overcome the obstacles experienced in the application of developing the character of nationalism through the habit of singing the Indonesia Raya song. The implementation of singing the national anthem Indonesia Raya to foster the character of nationalism in students implementing the policy of singing the national anthem Indonesia Raya to foster the character of nationalism in students is a lack of seriousness in students, and a lack of strict sanctions.